Retrospective analysis of 1286 oral and maxillofacial biopsied lesions of Iraqi children over a 30 years period. Issue 1 (April 2016) - Abdullah, Bashar Hamid; Jabbar Abdul Qader, Omar Abdul; Mussedi, Omar Shebli
Abstract: Objectives: To determine the prevalence of oral lesions by age and gender among the pediatric population in Iraq. Materials and methods: A review of the archives of the oral pathology department of Baghdad University from, 1970 Materials and Methods: A review of the archives of the oral pathology department of Baghdad University from 1970 to 2013 for all biopsies from children aged 0–15 years old. Results: A total of 1286 child specimens represented 11.98% of all biopsied lesions. The pyogenic granuloma was the most frequent lesion in children, and the periapical cyst was the most frequent lesion from an odontogenic origin. The incidence of malignant lesions was higher in the 0–3 age group than other groups. Conclusions: The majority of lesions were inflammatory or benign in nature, while 5.6% were malignant tumors. This study provides a data base for predicting the distribution of oral lesions in children with a different method from other similar studies.